SOME NEW MODELS FOR MULTIPROCESSOR INTERCONNECTION NETWORKS - Cvetković, Dragoš; Davidović, Tatjana; Jovanović, Irena M. (Yugoslav Journal of Operations Research, 2016)
A multiprocessor system can be modeled by a graph G. The vertices of G correspond to processors while edges represent links between processors. To ﬁnd suitable models for multiprocessor interconnection networks (brieﬂy MINs), one can apply tools and techniques of spectral graph theory. In this paper, we are extending some of the existing results and present several graphs that could serve as models for ecient MINs based on the small values of the previously introduced graph tightness. These examples of possible MINs arise as a result of some well-known and widely used graph operations. We also examine the suitability of strongly regular graphs (brieﬂy SRGs) to model MINs, and prove the uniqueness of some of them. Keywords: Spectra of graphs, Tightness, Interconnection networks, Graph operation.